Etika Praktis Penggunaan Artificial Intelligence (AI) dalam Studi Hadis Berlandaskan Nilai Islam dan Asas Etika Digital - Saifullah, Ma'rifah (IAIN KENDARI, 2026)
The advancement of Artificial Intelligence (AI) has significantly impacted hadith studies, particularly in the processes of verification, classification, and analysis of matn and sanad. While AI enables data-driven efficiency, it also introduces epistemological risks such as bias, information distortion, and hallucination that may threaten the authenticity of hadith scholarship. This study aims to formulate an ethical model for AI usage in hadith studies through the integration of Islamic values and digital ethics principles. Employing a qualitative library research approach, the data were analyzed using content analysis and thematic analysis. The findings reveal that integrating values of integrity, honesty, responsibility, and justice with principles such as fairness, transparency, and accountability produces a three-phase ethical model: pre-research, analytical process, and post-evaluation. The novelty of this study lies in positioning ethics not merely as a normative framework but as a methodological protocol that contextualizes the principles of ‘adalah and dhabt within digital verification. This model offers practical guidance to ensure both scientific validity and religious authority in contemporary hadith studies.